Creating Brave Space: Middle School Students Discuss Race - Beth A Beschorner; Kathleen Ferrero; Robbie Burnett (Middle Grades Review, 2021)
Racial disparities must be addressed in every sector in the United States (e.g., healthcare, education, incarceration, etc.) (Skiba et al., 2001). Mary, a middle school principal, created a series of conversations designed to help a small group of students begin to have more productive conversations about race. The purpose of the current study was to explore how educators create a space for middle school students to have inter- and intra- racial dialogues. Results suggest: (a) a demonstrated need and demand for spaces that support inter- and intra-racial dialogues; (b) the importance of strategic planning; and (c) the vital nature of developing relationships.
Keywords: Race; Racism; Middle School